Penerapan Metode PIECES Sebagai Evaluasi Tingkat Kepuasan Pengguna Aplikasi Telegram Sebagai Media Knowledge Sharing - Rini Fitriani; Joy Nashar Utamajaya (JURIKOM (Jurnal Riset Komputer), 2022)
Knowledge sharing has an important role in the student learning process in sharing knowledge with fellow friends and with teachers. Now there is a text messaging/messenger-based feature/application that helps students share knowledge such as telegrams. But whether the telegram application can run optimally in the knowledge sharing process or not, we don't know yet, for that it is necessary to analyze the performance of telegram. The purpose of this study is to determine the level of satisfaction of users of Telegram as an application for knowledge sharing. The method used to measure the level of user satisfaction is using the PIECES method. The results of this study indicate that the Telegram application gets an average value of 3.52 which indicates that users are very satisfied in using the Telegram application as a knowledge sharing application.